CAMTA1-immunonegative epithelioid hemangioendotheliomas of the liver: a clinicopathological and molecular analysis of seven cases - Nie, Yang; Jing, Wenyi; Zheng, Xuanxuan; He, Xin; Chen, Min; Zhang, Hongying (Frontiers in Oncology, 2025)
BackgroundEpithelioid hemangioendothelioma (EHE) is a rare malignant vascular tumor. Most EHEs (>90%) cases harbor WWTR1::CAMTA1 fusion gene, and CAMTA1 immunohistochemistry (IHC) is a highly sensitive and specific tool for EHE diagnosis. However, there exist CAMTA1-immunonegative cases, the majority of which harbor YAP1::TFE3 fusion, with a few cases having more rare fusions. Liver is one of the most common sites of EHE, where the CAMTA1 subtype dominates, and the other variants are extremely rare. Hence, we focused on the hepatic CAMTA1-immunonegative EHEs to analyze the clinicopathological and molecular features of these peculiar cases.MethodsThe SNOMED search of the hospital pathology files between January 2016 to November 2023 identified 57 hepatic EHEs and 7 cases were CAMTA1-immunonegative. Fluorescence in situ hybridization (FISH), next generation sequencing (NGS) and Sanger sequencing were performed to identify the genetic change of the 7 cases.ResultsThis series included 3 females and 4 males, aged from 33 to 64 years. All the 7 cases were negative for CAMTA1 IHC. Four cases were positive for TFE3 IHC and exhibited YAP1::TFE3 fusion. Another 3 cases were also negative for TFE3, while WWTR1::CAMTA1 fusion were detected by NGS in 1 case and demonstrated by FISH in all the 3 cases. Morphologically, among the 4 TFE3 rearrangement cases, 3 cases showed the TFE3-sutype morphologic appearance, while the histology of 1 case was similar to that of CAMTA1- subtype. In the 3 CAMTA1-rearranged lesions, 2 cases had classic EHE morphology, and 1 case exhibited atypical histology, with higher atypia and well-formed vessels. Surgical resection was performed on five cases and two cases were biopsied and received chemotherapy. Follow-up information was available in 6 patients (median 46 months), including 4 patients were alive without disease and 2 patients were alive with disease.ConclusionOur study reported 7 CAMTA1-immunonegative hepatic EHEs and most of them were TFE3-rearranged EHEs with morphology variation. Moreover, there does exist the CAMTA1-immunonegative but CAMTA1-rearranged EHE cases. Therefore, the diagnosis of EHE should be based on morphology, combined with CAMTA1 and TFE3 IHC, and if necessary, supplemented by genetic analysis including FISH and NGS, to establish correct diagnosis.